The Implementation of the Character Education Strengthening (PPK) Movement in the Junior High Schools (SMPN) Kerinci Regency - Ahmad Jamin; Deri Wanto; Sapriadi Sapriadi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The PPK movement launched by the government is a response to the phenomenon of moral decadence/character crisis that occurs in almost all levels and sectors of life, including in the world of education. The PPK movement aims to instill and strengthen the values of the nation's character in the education unit. This study aims to describe the implementation of the PPK movement in the SMPN Kerinci regency by using qualitative research design and case study approach, namely in SMPN 13, SMPN 15, and SMPN 48. Data were collected through observation, unstructured interviews, and documentation. The data collected was then analyzed with Miles and Huberman techniques with data reduction, display, and conclusion drawing stages. The implementation of PPK has been running quite well. It positively impacts strengthening students' character characterized by increased discipline, honesty, responsibility, creativity, social care, and so on. However, the implementation of the PPK movement still has some constraints as teachers do not understand the essence and urgency of the PKK movement comprehensively and completely. In addition to other factors such as inadequate learning facilities and resources and still lack of support from stakeholders and the community.